ON BECOMING A PROFESSIONAL ENGLISH TEACHER : THE PROFESSIONAL IDENTITY CONSTRUCTION THROUGH EMOTIONS - Syakira, Sitti; Abdullah, Fuad; Anwari, M. Rifqi Romdoni; Andriani, Agis; Hidayati, Arini Nurul; Anwar, Dede (English Education Department, 2023)
In teacher identity studies, limited attention has been generally paid to how the pre-service teachers constructed their identity by conveying various emotions in their practices. Most scholars identified the pre-service teacher's emotions during the teaching practices program. However, identifying these emotions during online teaching practices remains under-researched. Given this fact, this study probed how an English pre-service teacher’s emotions constructed his professional identity during online teaching practices. This study employed a narrative inquiry of an English pre-service teacher during online teaching practices in one of the senior high schools in Tasikmalaya, West Java, Indonesia. The data were collected from an English pre-service teacher’s reflective journals and analysed with narrative analysis (Labov, 1972). The findings revealed that the English pre-service teacher met various emotions manifested in his professional identity construction. There were five emotions experienced during online teaching practices, namely worrying, challenging, empathetic, enjoyable, and determined explored in seven critical activities of the professional practice process. During learning to teach, he could manage his negative emotions (i.e., worrying, challenging, empathetic) into positive emotions (i.e., enjoyable, determined). Therefore, his emotions experienced during online teaching practices implied that his professional identity commenced constructing in the seven activities of his professional construction process.